Study of Nuclear Spin Conservation in Ammonium Alkali Halide Crystals - Roy, R.S. (Asian Journal of Chemistry, 2010)
The mixed salt (NH4)cK1-cX (X = I, Br), prepared from aqueous solutions, can maintain a spin-temperature inversion. It is shown that both the mixed salts (1, Br) relax at similar rates and these rates increase with the temperature variation (T3). The findings and results have been discussed in the context of other works on these salts.